Regulatory cells and transplantation tolerance. - Cobbold, S; Waldmann, H (2013)
Transplantation tolerance is a continuing therapeutic goal, and it is now clear that a subpopulation of T cells with regulatory activity (Treg) that express the transcription factor foxp3 are crucial to this aspiration. Although reprogramming of the immune system to donor-specific transplantation tolerance can be readily achieved in adult mouse models, it has yet to be successfully translated in human clinical practice. This requires that we understand the fundamental mechanisms by which donor antigen-specific Treg are induced and function to maintain tolerance, so that we can target therapies to enhance rather than impede these regulatory processes. Our current understanding is that Treg act via numerous molecular mechanisms, and critical underlying components such as mTOR inhibition, are only now emerging.